A review of clinical and surgical outcomes of endoscopic endonasal skull base surgery in a Tertiary Center in Sarawak - Ng, Kevin Boon Han; Goh, Chin Hwee; Teo, Ting Hee; Wong, Albert Sie Hieng; Lim, Swee Lan; Ngian, Donald San Liew; Tang, Ing Ping (Researchgate, 2018)
Background: Endoscopic endonasal approach (EEA) for skull base tumor has been extensively developed in recent years.